Differences in Sugar Concentration on Flavonoid Levels in Roselle Kombucha (Hibiscus sabdariffa L.) As An Antioxidant Beverage - Izza, Arifah Nurul; Lestari, Catur Retno; Hidayat, Umar (Journal of Biomedical Sciences and Health, 2026)
Background: Kombucha is a fermented tea beverage produced using a symbiotic culture of bacteria and yeast (SCOBY). Sugar concentration plays an essential role in the fermentation process as it influences microbial metabolism and the formation of bioactive compounds. Roselle (Hibiscus sabdariffa L.) is rich in flavonoids and anthocyanins, which act as natural antioxidants. Objective: This study aimed to determine the effect of different sugar concentrations on flavonoid levels in roselle kombucha. Methods: This was an experimental study using a completely randomized design (CRD) with one factor, namely sugar concentration: F1 (15%), F2 (25%), and F3 (35%). Fermentation was carried out with the addition of SCOBY for 14 days at room temperature. Flavonoid levels were analyzed using a spectrophotometric method with quercetin as the standard. Data were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney test. Results: The highest average flavonoid level was found in F1 (sugar concentration 15%) at 0.015690%, while the lowest was in F3 (sugar concentration 35%) at 0.011364%. The Kruskal-Wallis test showed a significant difference among treatments (p = 0.002, p < 0.05). The Mann-Whitney test confirmed that all pairwise comparisons between treatments were significantly different. Sugar concentration significantly affects flavonoid levels in roselle kombucha. Conclusion: The 15% sugar concentration produced the highest flavonoid content, suggesting that low sugar formulation is preferable to maintain bioactive compounds and enhance antioxidant potential. Therefore, roselle kombucha with lower sugar concentration can be developed as a functional beverage to prevent degenerative diseases related to oxidative stress.